2018
DOI: 10.1080/03007995.2018.1470500
|View full text |Cite|
|
Sign up to set email alerts
|

Adherence to iron chelation therapy in patients who switched from deferasirox dispersible tablets to deferasirox film-coated tablets

Abstract: Adherence and persistence improved significantly after switching from DFX-DT to DFX-FCT for all diseases, but especially MDS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 16 publications
1
9
0
Order By: Relevance
“…Compliance (~ 90% mean relative consumed tablet count) and persistence (95-100%) rates with deferasirox FCT during this study were found to be on the higher side. Persistence rates (proportion of patients with continuous use of deferasirox FCT with no interruption for ≥ 30 days or ≥ 60 days) in this study are comparable to the real-world data on persistence in patients who switched from deferasirox DT (39-80%) to deferasirox FCT (60-96%) [1].…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…Compliance (~ 90% mean relative consumed tablet count) and persistence (95-100%) rates with deferasirox FCT during this study were found to be on the higher side. Persistence rates (proportion of patients with continuous use of deferasirox FCT with no interruption for ≥ 30 days or ≥ 60 days) in this study are comparable to the real-world data on persistence in patients who switched from deferasirox DT (39-80%) to deferasirox FCT (60-96%) [1].…”
Section: Discussionsupporting
confidence: 76%
“…Iron overload in chronic anemias represents a serious consequence of impaired hematopoiesis and repeated blood transfusions leading to end-organ damage, reduced quality of life, and decreased survival. Iron chelation therapy (ICT) can be a life-long requirement in chronic transfusion-dependent refractory anemias, including β-thalassemia, sickle-cell disease, and myelodysplastic syndrome (MDS) [1,2]. Despite the proven benefit of ICT, patient compliance to long-term ICT is challenging [3].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DFX is available in several forms, including Exjade® dispersible tablets (DFX-DT, oral administration once-daily, completely dissolved in liquids and consumed 30 min before meals on an empty stomach), Jadenu® granule formulation of DFX (DFX-GF),[ 8 ] and Nanojade® a new film-coated tablets formulation of DFX (DFX-FCT) in Iran pharmaceutical market. Nanojade® is a generic drug from Jadenu® (Novartis).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, improved palatability and compliancy, high bioavailability, and low gastrointestinal side effects promise a better treatment with Jadenu® for a long time. [ 8 11 ] DFX-FCT is prescribed based on body weight and has three dose strengths and is available in three dose strengths (90 mg, 180, and 360 mg). [ 11 ]…”
Section: Introductionmentioning
confidence: 99%